2008
DOI: 10.1111/j.1748-0361.2008.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Location for Tobacco Cessation: Rural–Urban Disparities in Quit Success in Underserved West Virginia Counties

Abstract: Tobacco control programs in rural West Virginia would do well to build upon the positive aspects of rural life while addressing the infrastructure and economic needs of the region. End-of-class quit success may usefully be viewed as a stage on the continuum of change toward long-term quit success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 20 publications
1
45
2
Order By: Relevance
“…Several targeted cessation trials in the USA86 88 89 92 and one in Australia93 reported relatively high quit rates, although these studies were generally small (100 participants or fewer). Two larger studies87 91 targeted ‘disadvantaged’ communities but attracted smokers with a range of SES; both reported greater success among high-SES individuals 91 87…”
Section: Smoking Cessation Supportmentioning
confidence: 99%
“…Several targeted cessation trials in the USA86 88 89 92 and one in Australia93 reported relatively high quit rates, although these studies were generally small (100 participants or fewer). Two larger studies87 91 targeted ‘disadvantaged’ communities but attracted smokers with a range of SES; both reported greater success among high-SES individuals 91 87…”
Section: Smoking Cessation Supportmentioning
confidence: 99%
“…Variables included age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and ‡ 51 years), education ( < high school, high school/General Educational Development (GED), and > high school), race (white vs. other), marital status at time of interview (never married, married/member of couple, and divorced/widowed/separated), employment (full-time, part-time, unemployed/disabled, other), occupation (professional as defined by a degree, skilled labor, unskilled labor, other), annual household income, and health insurance (private, government-assisted, none).…”
Section: Social and Demographic Characteristicsmentioning
confidence: 99%
“…The program was intensive and consisted of a medical examination, an eight-session educational and behavioral counseling program that included pharmacotherapy, and follow-up group meetings. When compared to urban residents, rural participants in the program were signifi cantly less likely to quit at the end of the intervention ( OR = 0.58; 95% CI 0.35, 0.94), after adjusting for characteristics known to infl uence cessation (Northridge et al, 2008). Second, Hahn and coworkers implemented a community-based approach to promote cessation among smokers residing in rural Kentucky (Hahn et al, 2005).…”
Section: Rural Smokersmentioning
confidence: 95%